The Spectator, 2002-03-07 - Spectator, Valdosta State University (Valdosta State University, 2002)
The Spectator, March 7, 2002 (DRAFT COPY). Vol. 70 no. 08. SGA prepares for SAC -- Spring is here or is it? -- Retreat part of larger picture -- Students, activists meet at VSU -- TKE responsible on four counts
The Spectator: The Unfiltered, Uncensored Voice of the Students
Born digital draft copy. Converted from QuarkXpress format to PDF. Some content may be incomplete from final print editions. Some fonts have been changed.
Keywords: Valdosta State University -- Periodicals